Nevirapine Concentrations During the First Month of Life and Maternal Efavirenz Washout in High-Risk HIV-Exposed Infants Receiving Triple Antiretroviral Prophylaxis - Suvaporn Anugulruengkitt (2019)
BACKGROUND: Triple-drug infant antiretroviral prophylaxis containing nevirapine (NVP) is increasingly used to prevent HIV transmission among neonates at high risk of HIV infection. Our aim was to describe NVP concentration from birth through the first month of life. METHODS: High-risk HIV-exposed neonates were enrolled in a prospective cohort in Thailand. High-risk neonates defined as maternal HIV RNA >50 copies/mL before delivery or mother received antiretroviral treatment for <12 weeks before delivery. Neonates received zidovudine (4 mg/kg) and lamivudine (2 mg/kg) twice daily, plus NVP (4 mg/kg) once daily (no lead-in) from birth to 6 weeks of life. Infant plasma samples were collected at 1, 2, 14 or 2, 7, 28 days of life. NVP trough concentrations (C24) were estimated using a population pharmacokinetic model and target C24 was ≥0.1 mg/L. "Washout" efavirenz (EFV) concentrations were assessed in infants whose mother received EFV-based antiretroviral treatment. RESULTS: A total of 48 infants were included: 25 (52%) were male and 12 (25%) were preterm (gestational age 34-37 weeks). Median (interquartile range) predicted NVP C24 were 1.34 mg/L (1.13-1.84), 2.24 (2.00-2.59), 2.78 (2.61-3.12), 2.20 (1.86-2.44) and 0.81 (0.58-0.98) on days 1, 2, 7, 14 and 28 of life, respectively. NVP C24 was not significantly different between term and preterm infants. All infants maintained NVP C24 ≥0.1 mg/L. EFV via placental transfer remained detectable in infants up to 7 days of life. CONCLUSIONS: NVP 4 mg/kg daily from birth provided adequate prophylactic concentrations during the first month of life in high-risk HIV-exposed neonates.